Dataset pertaining to paper "New insights on the radiative impacts of ozone-depleting substances" - Chiodo, Gabriel (ETH Zurich, Institute for Atmospheric and Climate Science, 2022)
Focusing on the period 1955-2005, we here present results from offline radiative forcing (RF) calculations from a global chemistry climate model. Using realistic distributions of ODS and consistent stratospheric ozone, we show that ODS dominate the adjusted stratospheric warming of the lower stratosphere, where CO2 has little radiative impact. We also show that the global mean RF of stratospheric ozone only cancels a fraction of the RF of ODS, leaving an important ODS contribution to anthropogenic forcing. Finally we show that the RF of ODS opposes Arctic amplification, its equator-to-pole gradient being larger than the one of CO2. NetCDF dataset